Pharmacokinetics and safety of a fixed-dose combination of pregabalin and thioctic acid in healthy volunteers: a randomized, open-label, phase 1 crossover study - Zárate, Edith; Bravo-Lamicq, Cecilia; Ocampo-Gutiérrez de Velasco, Diego Antonio; Arias-Carrión, Oscar (Frontiers in Pharmacology, 2025)
BackgroundPregabalin (PGB) is a first-line therapy for painful diabetic neuropathy (PDN), but its adverse effects limit use. Thioctic acid, also known as α-lipoic acid (ALA), exhibits antioxidant and neuroprotective properties. The pharmacokinetic interaction profile of their combination in humans remains incompletely characterized.MethodsIn this randomized, open-label, three-period, six-sequence, single-dose crossover study, 24 healthy adults (12 males, 12 females) received PGB (80 mg), ALA (400 mg), or their fixed-dose combination under fasting conditions, with 7-day washouts. Plasma concentrations were measured at 17 time points over 36 h using a validated UPLC–MS/MS method. Non-compartmental analysis was used to derive pharmacokinetic parameters (Cmax, tmax, AUClast, AUCinf, t½). Bioequivalence was assessed using geometric mean ratios (GMRs) and 90% confidence intervals (CIs).ResultsFor PGB, the GMRs (90% CIs) for Cmax and AUClast were 91.2% (82.5%–100.8%) and 90.4% (80.9%–100.9%), respectively. For ALA, the GMRs were 108.9% (90.6%–130.8%) for Cmax and 96.5% (87.7%–106.3%) for AUClast. All 90% CIs were within predefined bioequivalence ranges (80%–125% for PGB and ALA AUClast, 75%–133% for ALA Cmax). Adverse events were mild, transient, and resolved without intervention; no serious adverse events occurred.ConclusionIn this single-dose, Phase 1 trial in healthy volunteers, co-administration of PGB and ALA did not result in clinically significant pharmacokinetic interactions and was well tolerated. These findings provide preliminary pharmacokinetic evidence to support further clinical evaluation in patients with PDN.